Expression of CD133 in various premalignant and proliferative lesions - Rahmi Amtha; Indrayadi Gunardi; Ferry Sandra; Diah Savitri Ernawati (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: In Jakarta, oral squamous cell carcinoma (OSCC) usually detected in late stage with very low survival rate ofabout 1.1 years. OSCC may be preceded by premalignant lesion, so that early detection of the lesion may decrease the mortality rate due to oral malignancy. CD133 is a hematopoietic stem cell that play role in tissue regeneration, inflammation and tumor. Upregulated of CD133 was reported on tumor progression. Purpose: The aim of study is to determine circulating CD133 expression on premalignant (PML) and proliferative (PL) lesion. Method: Observational research was carried out on patients who seek treatment of PML and PL at Oral Medicine clinic. CD133 was taken from peripheral blood serum, examined using PCR. Data was analyzed by Chi square test. Result: 15 subjects (each of five subjects for PML, PL and control) consist of 40% male and 60% female. Age group of above 41 years old was most affected PML and PL (66.7%). Tongue is common site for oral lesion (40%). There is a significant different of circulating CD133 rate among all groups lesion (p=0.039). Conclusion: CD133 express differently in premalignant and proliferative lesions.